Atrial fibrillation fact sheet in Korea 2024 (part 1): epidemiology of atrial fibrillation in Korea - So-Ryoung Lee; Daehoon Kim; Sung Ho Lee; Woo-Hyun Lim; Kwang Jin Chun; Won-Seok Choe; Hyo-Jeong Ahn; Kyung-Yeon Lee; JungMin Choi; Bong-Seong Kim; Kyung-Do Han; Eue-Keun Choi (International Journal of Arrhythmia, 2024)
Abstract Background and objectives This study aimed to analyze and present updated trends in atrial fibrillation (AF) epidemiology within the Korean population, providing a foundation for planning and implementing appropriate management and treatment strategies for patients with AF. Patients and methods We used the Korean National Health Insurance Service database to evaluate the prevalence, incidence, comorbidities, and clinical adverse outcomes of patients with AF in Korea between 2013 and 2022. Results AF prevalence in Korean adults aged ≥ 20 years doubled (1.1 to 2.2%) between 2013 and 2022, with significant increases observed across various sex and age groups. Similarly, the number of newly diagnosed patients with AF per year increased steadily, with the incidence rising from 184 to 275 per 100,000 person-years, particularly among older populations. Over this period, the mean age of patients with AF increased from 67.7 to 70.3 years, and comorbidities prevalence and CHA2DS2-VASc score rose significantly, indicating a higher stroke risk. Compared with patients without AF, AF was associated with an increased risk of mortality (hazard ratio [HR]: 1.78), ischemic stroke (HR: 2.39), major bleeding (HR: 2.10), myocardial infarction (HR: 1.44), and heart failure admission (HR: 2.42). Conclusion AF prevalence and incidence have steadily increased between 2013 and 2022, with a more pronounced increase in older patients. Patients with AF are increasingly becoming a high-risk population and are at increased risk of clinical adverse outcomes compared to non-AF patients. Therefore, a sustained national effort to improve AF awareness and comprehensive care quality for patients with AF is required.